Effects of γ-polyglutamic acid on the physicochemical properties and microstructure of grass carp (Ctenopharyngodon idellus) surimi during frozen storage. (December 2020) - Tao, Lu; Tian, Lu; Zhang, Xiushan; Huang, Xin; Long, Haiying; Chang, Fangyuan; Li, Tuoping; Li, Suhong
Abstract: The cryoprotective effects of γ-polyglutamic acid (γ-PGA) on grass carp surimi during frozen storage at −20 °C were investigated. The results showed that γ-PGA significantly maintained the quality traits of frozen grass carp surimi. Among the different concentrations of γ-PGA, treatment with 0.8% γ-PGA represented highest cryoprotective effect on the grass carp surimi during frozen storage, and its cryoprotective effect was also better than that of a conventional cryoprotectant (SS treatment). During freeze-thaw process, the gel strength and Ca 2+ -ATPase activity treated with 0.8% γ-PGA were 40.7% and 31% higher than those of the control group, respectively. Moreover, after 84 days frozen storage, the addition of 0.8% γ-PGA increased the gel strength, salt-soluble protein content, Ca 2+ -ATPase activity and the whiteness by 87.1%, 50%, 70.8% and, 11.9%, respectively, compared to the control. Meanwhile, treatment with 0.8% γ-PGA primely maintained the gel structure and sensory score of frozen grass carp surimi as well. These results indicated that γ-PGA was a potential cryoprotectant applying for the production, storage and transportation of surimi. Highlights: γ-PGA inhibited the denaturation of grass carp surimi during frozen storage. γ-PGA maintained the quality traits of frozen grass carp surimi. 0.8% γ-PGA revealed better cryoprotection effect than a conventional cryoprotectant.